Party Formation through Petitions: The Whigs and the Bank War of 1832–1834. Issue 2 (6th October 2015) - Carpenter, Daniel; Schneer, Benjamin
Abstract : When President Andrew Jackson removed the public deposits from the Bank of the United States, he set off an economic and political crisis from which, scholars agree, the Whig Party emerged. We argue that petitioning in response to removal of the deposits shaped the emergence of the Whig Party, crystallizing a new line of Jacksonian opposition and dispensing with older lines of National Republican rhetoric and organization. Where petitioning against removal of the deposits was higher, the Whigs were more likely to emerge with organization and votes in the coming years. We test this implication empirically by using a new database of petitions sent to Congress during the banking crisis. We find that petitioning activity in 1834 is predictive of increased support for Whig Party candidates in subsequent presidential elections as well as stronger state Whig Party organization.